Energy Efficiency Measurement Method of Operating Ship Based on Data Mining. Issue 3 (March 2021) - Li, Fangxuan
Abstract: Energy conservation in ship operation has become an important measure to reduce global greenhouse gas emissions. Therefore, it is necessary to carry out effective measurement of the energy efficiency of operating ships, so as to lay a foundation for their energy consumption. Based on this, this study designed a measurement method of energy efficiency of operating ships based on data mining. On the basis of analyzing the energy efficiency characteristics of operating ships, the paper analyzes the vessel resistance and the transfer of energy demand. Based on this, the energy efficiency measurement algorithm of operating ships is designed. By standardizing the energy consumption value of ships during navigation, the energy efficiency conversion of operating ships can be suppressed and utilized to avoid excessive energy consumption of ships during navigation and effectively control the Greenhouse gas emissions during navigation.